2013
DOI: 10.1016/j.healthplace.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of neighborhood environments and childhood obesity: Evidence of harmful gender inequities among Portuguese children

Abstract: This study investigates the links between parents' perceptions of their social and built residential environment and obesity among Portuguese school boys and girls. A total of 1885 children, 952 girls and 933 boys, aged 3.0-10.0 years, were observed. The children's weight and height were measured, and their parents filled out the "Environmental Module" questionnaire of the International Physical Activity Prevalence Study. Age and sex-specific BMI cut-off points were used to define being overweight/obese. Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
(52 reference statements)
1
23
0
4
Order By: Relevance
“…Studies have shown that parental perceptions are associated with the weight status of children and adolescents, who are under the responsibility of an adult and do not have autonomy over their decisions [24,25]. In addition, walking and cycling for transportation by youth have been associated with objective measurements of community design and transportation attributes such as distance to destinations, sidewalks, and traffic safety [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that parental perceptions are associated with the weight status of children and adolescents, who are under the responsibility of an adult and do not have autonomy over their decisions [24,25]. In addition, walking and cycling for transportation by youth have been associated with objective measurements of community design and transportation attributes such as distance to destinations, sidewalks, and traffic safety [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that the absence of sidewalks and bicycle lanes-or their poor maintenance-limit the active mobility and place at risk the safety of those who decide to use them. This situation may result in decreased PA and, consequently, in the weight gain of the local population [24,25,32]. About neighborhood esthetics, Mota et al [32] found that more physically active adolescents are the ones who care about the recreational opportunities and beauty of the neighborhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, PA is influenced by gender both in children and in adolescents (Inchley, Kirby, & Currie, ; Křen, Kudláček, Wąsowicz, Groffik, & Frömel, ), with girls having lower levels of habitual PA and sport participation than boys (Křen et al, ; Nogueira, Ferrao, et al, ; Pate et al, ; Santos, Vale, Miranda, & Mota, ). Furthermore, it has been suggested that gender and environment interact and that this interaction may enhance the impact of the local environment on PA (Nogueira, Gama, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that gender and environment interact and that this interaction may enhance the impact of the local environment on PA (Nogueira, Gama, et al, ). According to some studies, the PA of adolescent girls seems to be more sensitive to features of the built environment, while the PA of adolescent boys showed a particular sensitivity to the social environment, mainly to peer influences (Evenson et al, ; Hume, Salmon, & Ball, ; Nogueira, Ferrao, et al, ; Santos et al, ).…”
Section: Introductionmentioning
confidence: 99%